Discrete Time Analysis of Multi-Server Queueing Systems in Material Handling and Service - Matzka, Judith M. (Wissenschaftliche Berichte des Institutes für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2011)
In this doctoral thesis, performance parameters of multi-server queueing systems are estimated under general stochastic assumptions. We present an exact calculation method for the discrete time distribution of the number of customers in the queueing system at the arrival moment of an arbitrary customer. The waiting time distribution and the sojourn time distribution are estimated exactly, as well. For the calculation of the inter departure time distribution, we present an approximation method.